Andrographolide suppresses non-small-cell lung cancer progression through induction of autophagy and antitumor immune response. (May 2022) - Wang, Xuan-Run; Jiang, Ze-Bo; Xu, Cong; Meng, Wei-Yu; Liu, Pei; Zhang, Yi-Zhong; Xie, Chun; Xu, Jing-Yi; Xie, Ya-Jia; Liang, Tu-Liang; Yan, Hao-Xin; Fan, Xing-Xing; et al.
Abstract: Despite recent advances in diagnosis and therapeutic strategies, treatment of non-small-cell lung cancer (NSCLC) remains unsatisfactory in terms of prognosis. Andrographolide (AD), a principal active component of Andrographis paniculata (Burm.f.) Nees, exerts anti-cancer therapeutic properties. AD has been used for centuries in China for clinical treatment of viral infections. However, the pharmacological biology of AD in NSCLC remains unknown. In this study, AD regulated autophagy and PD-L1 expression in NSCLC. Molecular dynamics simulations indicated that AD bound directly to signal transducer and activator of transcription-3 (STAT3) with high affinity. Proteomics analysis indicated that AD reduced the expression of tumour PD-L1 in NSCLC by suppressing JAK2/STAT3 signalling. AD modulated the P62-dependent selective autophagic degradation of PD-L1 by inhibiting STAT3 phosphorylation. In vivo study revealed that AD suppressed tumour growth in H1975 xenograft mice and Lewis lung carcinoma cell models, and better efficacy was obtained at higher concentrations. AD prolonged the survival time of the mice and enhanced the treatment efficacy of anti-PD-1 mAb immunotherapy by stimulating CD8 + T cell infiltration and function. This work elucidated the specific mechanism by which AD inhibited NSCLC. Treatment with the combination of AD and anti-PD-1 mAb immunotherapy could be a potential strategy for patients with NSCLC. Graphical Abstract: ga1 Highlights: Andrographolide regulates autophagy and PD-L1 expression in NSCLC. Andrographolide reduces the expression of tumour PD-L1 in NSCLC by suppressing JAK2/STAT3 signaling. Andrographolide modulates the p62-dependent selective autophagic degradation of PD-L1 by inhibiting STAT3 phosphorylation. Andrographolide enhances the treatment efficacy of anti-PD-1 mAb immunotherapy by stimulating CD8 + T cell infiltration and function.